Complex Fractures of the Limbs Diagnosis and Management - Rodríguez-Merchán, E. Carlos; Rubio-Suárez, Juan Carlos (Springer International Publishing : Imprint: Springer, 2014)
This book provides up-to-date guidance on the diagnosis and treatment of the most important complex fractures of the limbs, including fractures of the proximal and distal humerus, fractures and dislocations of the elbow, fractures of the distal radius, pelvis, acetabulum, distal femur, proximal tibia, tibial pilon, calcaneus and osteoporotic knee fractures. The most complex articular fractures are analyzed, soft tissue coverage is reviewed, and the management of open fractures and nonunions is described and illustrated. Other chapters consider damage control management and immediate bone fixation in the polytrauma patient, skeletal reconstruction and rehabilitation of complex fractures of the limbs. The book offers guidance to orthopaedic surgeons on which treatment options afford the best preservation of fully functional joints around the fractured bone. With this goal in mind, the authors have developed strategies that can restore full articular function of the limbs in both the short and the long term. Complex Fractures of the Limbs will be an invaluable aid to orthopaedic surgeons in treating patients with this very common and important clinical problem.